Prognostic Biomarker NUMB Is Inhibited by Breast Cancer Cell Exosomes to Promote Breast Cancer Progression - Xue Qin; Youde Cao (Journal of Immunology Research)
Objective. To clarify the regulation of breast cancer cell-derived exosomes on breast cancer and the expression of the NUMB endocytic adaptor protein (NUMB) protein. Methods. The exosomes of breast cancer cell line MDA-MB-231 were isolated. The exosomes were subsequently labeled with PKH67 and added to breast cancer MDA-MB-231 cells cultured in vitro. Transwell and clone formation assays were performed to detect cell migration, invasion, and clone formation. Meanwhile, Western blot and qPCR were conducted to determine the regulation of NUMB expression by exosomes in breast cancer cells. Furthermore, NUMB overexpressed lentivirus was supplemented to validate the recovery. Results. The number of migrating and invasive breast cancer cells in the exosome-treated group was significantly increased compared with the control group. Moreover, the number of breast cancer cell clones in the exosome-treated group was increased than in the control group. However, the NUMB expression in breast cancer cells treated with exosomes revealed a substantial decrease, indicating that the exosomes of breast cancer cells could inhibit NUMB expression. NUMB overexpressed lentivirus supplementation markedly suppressed cell migration, invasion, and proliferation of breast cancer cells compared with exosome group. Conclusion. Taken together, the exosomes of breast cancer cells could inhibit the expression of NUMB and promote the migration, invasion, and cell clone formation of breast cancer cells.